Angiogenesis Inhibitors in Small Cell Lung Cancer - Montanino, Agnese; Manzo, Anna; Carillio, Guido; Palumbo, Giuliano; Esposito, Giovanna; Sforza, Vincenzo; Costanzo, Raffaele; Sandomenico, Claudia; Botti, Gerardo; Piccirillo, Maria C.; Cascetta, Priscilla; Pascarella, Giacomo; et al. (Frontiers in Oncology, 2021)
Inhibition of angiogenesis has been demonstrated to be an efficacious strategy in treating several tumors. Vascular endothelial growth factor (VEGF) is the most important protein with proangiogenic functions and it is overexpressed in small cell lung cancer (SCLC). Bevacizumab, a monoclonal antibody directed against VEGF, showed a promising activity in combination with etoposide and cisplatin as first-line treatment of patients with extended stage (ES)-SCLC and two randomized studies confirmed that bevacizumab improved PFS, but failed to prolong OS. Instead, disappointing results have been observed with endostar, sunitinib, sorafenib, vandetanib and thalidomide in combination with chemotherapy in the first line setting, with sunitinib in the maintenance setting, with sunitinib, cediranib and nintedanib as single agents or ziv-aflibercept in combination with topotecan in second line setting. Only anlotinib improved OS and PFS as third line therapy in Chinese patients with SCLC and it was approved with this indication in China. Future challenges are the evaluation of the role of angiogenesis inhibitors in combination with immune-checkpoint inhibitors and chemotherapy in SCLC patients and the identification of predictive biomarkers of response to both agents.